Model-Driven Architecture for Accelerating the Development of Tourism Applications - Lahbib Naimi; Lamya Benaddi; Charaf Ouaddi; Adnane Souha; Hamza Abdelmalek; Abdeslam Jakimi (IEEE Access, 2025)
The tourism sector has witnessed a significant shift towards digital transformation, with mobile and web applications becoming essential tools for enhancing tourist experiences. Despite their potential, the development of these applications is often hindered by challenges such as platform heterogeneity, rapid adaptability, and integration complexity. This paper proposes a Model-Driven Architecture (MDA) approach to address these challenges and accelerate the development of tourism applications. The approach introduces the use of the 6As framework as a domain model, alongside systematic model transformations, to streamline the development process. A detailed case study demonstrates the transformation of a class diagram into a functional backend, showcasing the advantages of automation, scalability, and maintainability. Validation results reveal significant improvements in development time compared to traditional manual methods. This contribution highlights the potential of MDA to simplify the development of complex systems while ensuring quality and adaptability. Future work aims to enhance the methodology by incorporating additional architectural patterns, expanding support for diverse platforms, and integrating advanced validation techniques.